Homebound : a novel - Elan, Portia (Good morning America book club., 2026)
"It's 1983 and Becks can't wait to get the hell out of Cincinnati. She's nineteen, blasting her Walkman, and hiding from the fact that her beloved uncle, the only person who understood her, is dead But she has work to do: he left her a half-finished game to complete--one last collaboration to find her way out of loneliness. Little does she know, what Becks is making will echo far into the future and shape the lives of a scientist, a sentient automaton, and a flinty sea captain in ways she cannot imagine. All are bound together by their search for connection--and by a futuristic traveler on a mysterious mission through space."--Provided by publisher.